2014
DOI: 10.1007/978-1-4899-8032-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Nesprins in Cell Stability and Migration

Abstract: Nesprins are a family of proteins that are primarily known for their localization along the nuclear envelope. Together with inner nuclear membrane SUN proteins, they form the core of the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex that traverses both nuclear membranes to connect the cytoplasm and the nuclear interior. Based on their structure and interactions, Nesprins integrate the nucleus into the cytoskeleton of a cell. Mutations in Nesprins have been identified in a group of human diseases tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Nesprins are further structurally characterized by a spectrin repeat rod domain and a variable N-terminal domain which interacts with cytoskeletal elements including actin and plectin ( Wilhelmsen et al, 2005 ). To date the LINC complexes have been implicated in a variety of cell processes including nuclear size, shape and positioning, cell migration and polarity as well as mechano-sensory signal transduction (reviewed in Lombardi and Lammerding, 2011 ; Razafsky et al, 2011 ; Neumann and Noegel, 2014 ) In addition to roles in NE embedded LINC complexes at the ONM, Nesprin-2a, lacking a transmembrane domain has been shown to exist within the nuclear interior and Nesprin-2 has been shown to directly interact with Lamin A ( Haque et al, 2010 ; Yang et al, 2013 ).…”
Section: The Nuclear Membranementioning
confidence: 99%
“…Nesprins are further structurally characterized by a spectrin repeat rod domain and a variable N-terminal domain which interacts with cytoskeletal elements including actin and plectin ( Wilhelmsen et al, 2005 ). To date the LINC complexes have been implicated in a variety of cell processes including nuclear size, shape and positioning, cell migration and polarity as well as mechano-sensory signal transduction (reviewed in Lombardi and Lammerding, 2011 ; Razafsky et al, 2011 ; Neumann and Noegel, 2014 ) In addition to roles in NE embedded LINC complexes at the ONM, Nesprin-2a, lacking a transmembrane domain has been shown to exist within the nuclear interior and Nesprin-2 has been shown to directly interact with Lamin A ( Haque et al, 2010 ; Yang et al, 2013 ).…”
Section: The Nuclear Membranementioning
confidence: 99%
“…1). Loss of nesprins leads to risk of nuclear structural instability, including nuclear shape, size and chromatin organization, which is implicated in tumorigenesis (68). Furthermore, nesprin-1 downregulation is reported in lung cancer, and synaptic nuclear envelope protein 1 gene mutation is observed in pancreatic cancer with metastasis (69).…”
Section: Nuclear Abps In Cancer Cellsmentioning
confidence: 99%
“…160 Nonetheless, recent work has indicated that nucleoskeleton involvement in basic cellular processes such as maintenance of nuclear shape and size, centrosomal positioning, cell migration and signal transduction, and DNA damage repair all likely contribute to the formation of a wide range of cancers. 161,162 Therapeutic target identification and screening approaches Thus far, there are no treatments to "cure" any of the nucleoskeleton-linked muscular dystrophies. Nonetheless, some approaches are currently being investigated.…”
Section: Mutations In Nucleoskeletal Proteins Cause Human Diseasementioning
confidence: 99%